Calcineurin-NFAT dynamics correspond to cardiac remodeling during aortic banding and debanding, mimicking aortic valve replacement - Lunde, Ida G.; Skrbic, Biljana; Sjaastad, Ivar; Christensen, Geir; Carlson, Cathrine R.; Tønnessen, Theis (Frontiers in Molecular Medicine, 2022)
Aortic valve stenosis (AS) is a major health problem. Extensive myocardial remodeling increases operative risk and might lead to incomplete reverse remodeling with persisting symptoms after aortic valve replacement (AVR), making optimal timing of AVR a clinical challenge. The pathogenesis behind incomplete reverse remodeling is unclear. Central among signaling pathways in the remodeling heart is the pro-hypertrophic Ca2+-activated calcineurin and its downstream nuclear factor of activated T-cell (NFATc1-c4) transcription factors. We investigated calcineurin-NFATc dynamics in patient and mouse hearts during remodeling and reverse remodeling. Myocardial biopsies were obtained from AS patients during AVR and left ventricles harvested from mice subjected to aortic banding (AB) and debanding (DB). Transcript and protein of the NFATc-responsive gene regulator of calcineurin 1-4 (RCAN1-4) and luciferase activity in NFAT-luciferase mice were used as read-outs for calcineurin-NFATc activity. Calcineurin-NFATc activation was sustained through AB 24 hrs-18 weeks and elevated in AS patients. All four NFATc isoforms were elevated in AS, while NFATc4 was persistently elevated during chronic remodeling after AB in mice. NFAT activation remained reversible when AB for one week was followed by DB for one week, and accompanied functional improvement. However, when DB for one week followed AB for four weeks, NFAT activation was not reversed. In conclusion, calcineurin-NFAT dynamics correspond with cardiac remodeling and reverse remodeling during experimental AB and DB. Our data suggest that calcineurin-NFATc attenuation is important for reverse remodeling and outcome after AVR for AS.